Produção de hidrogênio por fotofermentação empregando co-culturas de bactérias - Moreira, Felipe Santos (2020)
Hydrogen production by biological is a sustainable alternative because it demands a low amount of energy for its production and has the capacity to use renewable raw materials as substrates. The conversion of organic compounds to hydrogen in the photofermentation process has attracted interest in their use, as it presents high theoretical substrate conversion yields. Combining different groups of bacteria grown in a single bioreactor provides advantages of simple handling, reduced fermentation time and high yield rates. In this present study, the objective was study the production of hydrogen by photofermentation using Enterobacter cloacae bacteria and photosynthetic purple non-sulfur bacteria: Rhodobacter capsulatus and Rhodopseudomonas palustris. The carbon sources used were glucose P.A. and the whey permeate (70 % lactose), that is an agroindustrial residue. The assays were carried out in fed batch reactor, checking the influence of: culture medium, sugar source, light, inert gas and substrate feeding forms. The Enterobacter cloacae microorganism showed satisfactory results for hydrogen production, using nitrogen or argon as inert gases, with or without the presence of light, characterizing its ability to metabolize under different conditions. Evaluating the culture media in the co-culture system, the nutrient broth reaction medium reached a maximum productivity of 201.15 mmol H2/L.day, with Enterobacter cloacae and Rhodobacter capsulatus (whey permeate), since its composition offers the amount of carbon and total nitrogen, derived from meat extract and peptone reagents, present in the medium composition, directly impacting the hydrogen production. In the tests with the alternation feeding of the carbon source to the reaction medium, promoted the highest hydrogen productivity, being the maximum of 319.35 mmol H2/L.day in the 180 hours time. The metabolites formed during the fermentation process were obtained in significant quantities, especially butyric, lactic and acetic acid, predominating the metabolic pathways of hydrogen production.